КЛИНИЧЕСКИЙ ОПЫТ РЕАЛИЗАЦИИ ИНВАЗИВНОЙ СТРАТЕГИИ ЛЕЧЕНИЯ ОСТРОГО КОРОНАРНОГО СИНДРОМА БЕЗ СТОЙКОГО ПОДЪЕМА СЕГМЕНТА ST НА ЭКГ - Ю. А. Прилуцкая; Л. И. Дворецкий (Архивъ внутренней медицины)
In article authors discuss invasive strategy of treatment of patients with acute coronary syndrome without ST elevation. 221 cases from CCU of hospital № 7 were analysed. There are some problems in pre-clinical diagnosis (half of cases were excluded diagnosis of acute coronary syndrome write after hospitalisation) and hight specifity of preliminary clinical diagnosis, that was approved in 82% of cases. Only 26% of patients with acute coronary syndrome without ST elevation were refered to surgery (in 15 cases — percutaneous coronary intervention, in 3 — coronary artery bypass grafting). After analisation of medical histories authors find out patients to whom surgery was needed but wasn’t prescribed (in 29 cases — contrindications, in 23 — recomendation to deferred coronaroangiography and 15 were discharged without stress test performance. In situation we will use new diagnostical tools and methods we can find more cases of acute coronary syndrome without ST elevation.